Novel Clostridium thermocellum type I cohesin-dockerin complexes reveal a single binding mode - Brás, Joana L. A. (2019)
PEst-C/EQB/LA0006/2011 This work was supported by Fundação para a Ciência e a Tecnologia Grants PEst-C/EQB/LA0006/2011, PTDC/BIA-PRO/69732/2006, PTDC/QUI-BIQ/100359/2008, and PTDC/BIA-PRO/103980/2008. Supported by Fundação para a Ciência e a Tecnologia individual fellowship SFRH/BD/38667/2007.